2014
DOI: 10.1007/s40620-014-0126-4
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, cysteine, folate and vitamin B12 status in type 2 diabetic patients with chronic kidney disease

Abstract: Hyperhomocysteinemia (hHcy) is a risk\ud factor in the progression of chronic kidney disease (CKD).\ud In type 2 diabetes (T2D), hHcy is strongly associated with\ud increased risk of cardiovascular disease. Vitamin B12 and\ud folic acid supplementation have been reported to lower\ud homocysteine (tHcy) levels, but no data on plasma tHcy,\ud cysteine (Cys), folate and vitamin B12 levels in T2D-CKD\ud patients are reported.\ud Procedures tHcy and Cys levels were analyzed in 178\ud T2D-CKD patients by high perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 26 publications
4
27
1
1
Order By: Relevance
“…Di Daniele et al [55] demonstrated that the Italian MD in nephropatic patients could be a useful tool in the treatment of cardiovascular comorbidity related to renal dysfunction, causing a significant decrease in serum homocysteine (Hcy), dependant on a methylenetetrahydrofolate reductase genotype. In fact, Hcy, during the autoxidation process, induces impairment of the endothelium by producing ROS, with consequent involvement in atherosclerosis [56,57]. All these studies support that adherence to the MD with EVOO can modify inflammation, regardless of shared genetic and environmental factors.…”
Section: Oleuropein As An Anti-inflammatory and Cvd Protective Agentmentioning
confidence: 76%
“…Di Daniele et al [55] demonstrated that the Italian MD in nephropatic patients could be a useful tool in the treatment of cardiovascular comorbidity related to renal dysfunction, causing a significant decrease in serum homocysteine (Hcy), dependant on a methylenetetrahydrofolate reductase genotype. In fact, Hcy, during the autoxidation process, induces impairment of the endothelium by producing ROS, with consequent involvement in atherosclerosis [56,57]. All these studies support that adherence to the MD with EVOO can modify inflammation, regardless of shared genetic and environmental factors.…”
Section: Oleuropein As An Anti-inflammatory and Cvd Protective Agentmentioning
confidence: 76%
“…1). Cystine levels could be elevated as a result of increased oxidative stress, or very early renal dysfunction (Buckley & Milligan, 1978; Hargrove & Wichman, 1987; Wijekoon, Brosnan & Brosnan, 2007; Pastore et al, 2015). Cysteine inhibits tyrosine aminotransferase activity, and can lead to an increased plasma tyrosine level (Buckley & Milligan, 1978; Hargrove & Wichman, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the species found to be decreased in CKD are among those that strengthen gut barrier function [16,36,37]; produce anti-inflammatory [46,71,73,109], NO [16,47], CDCA, UDCA [50,[83][84][85], GABA [60,61,110], Ach [65,107,108], and the vitamin B complex [17, 52-54, 81, 82]; increase the production of gut hormones with anti-inflammatory properties [57][58][59][76][77][78][79]; increase anti-inflammatory vagal activity [90,93,97]; and decrease pro-inflammatory renal sympathetic activity. Interestingly, CKD is associated with gut barrier dysfunction, an increase in uremic toxins [101], elevated renal sympathetic activity [111], lower group B vitamin levels [112][113][114] and NO [115], and a reduction in vagal activity [116], which may stem from the gut dysbiosis found in patients with CKD. Therefore, we can suggest that a healthy gut microbiota can protect from CKD, whereas gut dysbiosis takes part in the development and progression of CKD through a number of pathways that manipulate host inflammatory activity.…”
Section: Gut-kidney Crosstalk and Inflammation In The Development Of Ckdmentioning
confidence: 99%